2013
DOI: 10.7243/2050-0866-2-16
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes control and the influence of family functioning

Abstract: Background: The link between glycaemic control of type 1 diabetes and family functioning is complex, with the existing literature largely focussing upon the association between clear patterns of disturbances in family functioning and suboptimal diabetic control. The more subtle changes to family function that might influence the degree of successful management of a child's diabetes have been less well studied. Methods: This study sought to explore whether suboptimal glycaemic control was associated with variat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
2
1
2
Order By: Relevance
“…Similarly, previous studies showed that the HbA1c values of young individuals with diabetes were high. This may have been caused by poor diabetes management . The present study found that there was a weak relationship between metabolic control and duration of life with diabetes.…”
Section: Discussioncontrasting
confidence: 52%
“…Similarly, previous studies showed that the HbA1c values of young individuals with diabetes were high. This may have been caused by poor diabetes management . The present study found that there was a weak relationship between metabolic control and duration of life with diabetes.…”
Section: Discussioncontrasting
confidence: 52%
“…This agrees with findings from other studies which have shown that glycaemic control is related to family functioning. 49,50 This finding could be explained by the central role a family plays in patient management, especially in chronic illness like diabetes in our environment. This role in some situations can engender a positive outcome and in some may have a negative effect.…”
Section: Discussionmentioning
confidence: 99%
“…Selon notre étude, 66% des femmes en âge avancé sont obèses ou ayant un surplus de poids 26,90 ± 5,80 kg/m 2 , par conséquent, renferment généralement assez de masse grasse. Dans notre étude, beaucoup de femmes ont été victimes de cette maladie et parfaitement ignoraient la survenance ou l'apparition du diabète contrairement aux mères impliquées dans l'étude d'Angleterre (Whitehead et Dimmock, 2013).…”
Section: Causes De L'apparition Du Diabèteunclassified
“…L'ignorance de l'antécédent familial et de surcroît, l'incapacité d'effectuer des analyses biologiques assez régulièrement, dû au coût élevé des examens biologiques et à la faiblesse du revenu des ménages, expliquent nos résultats. Une étude réalisée en Angleterre (Whitehead et Dimmock, 2013) indique qu'il faut un dépistage précoce, ce qui n'est pas le cas au Burkina Faso. Pour éviter des complications futures de la maladie qui est silencieuse, un dépistage précoce est à effectuer lors des inscriptions dans les structures de formations d'éducations et lors des recrutements pour un poste de travail, ce qui permet de les prendre en charge dès lors qu'ils sont positifs au diabète sucré.…”
Section: Causes De L'apparition Du Diabèteunclassified